Analysis of interactions between potent inhibitors of ATP sulfurylase via molecular dynamics. Issue 8 (23rd May 2016) - dos Santos, Elias Silva; Gritta, Dermeval Heitor Souza; de Almeida, Jailton Souza
Abstract : The dynamic behaviour of adenosine triphosphate sulfurylase (ATPs) is analysed to investigate its energetic interactions with inhibitors recently studied theoretically and tested experimentally. The interactions between ATPs and three inhibitors namely, 2, 2′-azino-di-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS), butylated hydroxytoluene (BHT), and 3-tert-butyl-4-hydroxyanisole (BHA) in aqueous solution were studied via molecular dynamics simulations. The results of the absolute and relative free energies reveal the existence of synergism in the system. Additionally, the system demonstrates strong steric effect between ABTS and BHA that is not only due to the size of these inhibitors but also their surroundings.